Pola Aktivitas Pengolahan Pertanian Jagung yang Berdampak pada Kerusakan Lingkungan di Kabupaten Gorontalo - Bambang Mamangkay; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun; Iswan Dunggio (JAMBURA GEO EDUCATION JOURNAL, 2023)
The aim of the research was to find out the pattern of corn agricultural processing activities that were consistent or not carried out by farmers and the impact of the corn processing process in Gorontalo Regency..The data collection method used a questionnaire, and the sample in this study was the Gorontalo Regency Corn Farmers Association (GAPOKTAN) which was determined using the slovin formula with an estimation error of 10%. The method of collecting data on corn processing activities uses the Proportional Random model with a population of land managed by corn farmers in Gorontalo Regency. Data analysis for drawing conclusions using the Guttman approach. The results of the study found patterns of corn agricultural processing activities in Gorontalo District that were consistently carried out, namely on pre-planting indicators including land clearing using pruning machines, use of pesticides, and burning of straw biomass and pastures. The indicators for planting the types of seeds used are Bisi and NK in one year 2 harvests. Treatment indicators include: the use of synthetic fertilizers, and the use of weed killer pesticides, harvest indicators include the activity of picking up the harvest, peeling, and delivering the harvest to the point of sale. In the processing of land, farmers have an advantage if the yield is above 5 tons and a loss if the yield is below 3 tons. The findings from this study are that the pattern of corn agricultural processing activities in the form of burning biomass, burning energy from conventional machines, and using fertilizers and pesticides is very massive which has an impact on environmental damage. In the processing of land, farmers have an advantage if the yield is above 5 tons and a loss if the yield is below 3 tons. The findings from this study are that the pattern of corn agricultural processing activities in the form of burning biomass, burning energy from conventional machines, and using fertilizers and pesticides is very massive which has an impact on environmental damage. In the processing of land, farmers have an advantage if the yield is above 5 tons and a loss if the yield is below 3 tons. The findings from this study are that the pattern of corn agricultural processing activities in the form of burning biomass, burning energy from conventional machines, and using fertilizers and pesticides is very massive which has an impact on environmental damage.